Positive Discipline and Class Agreements: An Effective Approach to Enhancing Character and Moral Values in Elementary School Students - Prihatiningsih; Maryani, Enok; Muryanto, Rusdiono (Universitas Pendidikan Ganesha, 2024)
The development of moral values in fifth-grade elementary school students requires a positive discipline approach to enhance their discipline and moral attitudes. This study aims to analyze the effectiveness of implementing positive discipline through class agreements in the development of students' moral values. The research method employed is descriptive with a qualitative approach. The sample consists of 26 fifth-grade students from class V-A, with data collection techniques including observation and interviews. Data analysis was carried out using the Miles and Huberman method, which includes data reduction, data presentation, and drawing conclusions. The results show that 44% of students believe that class agreements play a role in shaping the moral value of discipline, 54% of students consider the consequences applied in the class agreements to be moderate, 50% of students did not repeat the same violations, and 88% of students feel that class agreements influenced changes in their moral values or attitudes. These findings are supported by observation results conducted at various stages of implementing class agreements, from identification to follow-up. Based on these results, it can be concluded that the implementation of class agreements is effective in influencing the development of moral values in fifth-grade elementary school students.